State-Level Spending on Children Associated with Unequal Benefits to School Readiness. - Morrissey, Taryn W.; Engel, Katherine; Jackson, Margot I. (Maternal & Child Health Journal, 2025)
Objectives: To examine associations between state-level public investments in programming for children and parents' reports of their children's kindergarten readiness. Methods: We use regression approaches with publicly available, nationally representative data to examine how time and state variation in public spending on children relates to parents' concerns about children's development. We link data on annual state-level spending on health and early learning from the Urban Institute's State-by-State Spending on Kids Dataset and the National Institute for Early Education Research to child-level data from the 2003/2004, 2007/2008, and 2011/2012 waves of the National Survey of Children's Health (NCHS), focusing on a subsample of parents with one or more children under age six (N = 56,736). Results: Child-related public spending on both health and early education is associated with decreases in parents' concerns about their children's physical health and motor development. A 15% increase in average health spending and early education spending per child per year is associated with a reduction in parents' concerns about children's health and motor development of about 3% and 2% of a standard deviation (SD), respectively. Associations between spending and concerns about early learning and social-emotional development are negative but not significant. Among socioeconomically disadvantaged or racial and ethnic minority parents, spending is associated with smaller reductions in concerns. Conclusions for Practice: Public spending on children is associated with fewer parents' concerns about their children's development, but less so among disadvantaged families. It is possible that public spending levels are not adequate to narrow disparities in early opportunity and outcomes. Significance: What is Already Known on this Subject: Prior research indicates that state-level public investments in children are positively related to family well-being, but their association with young children's readiness for kindergarten is unclear. What this Study adds: This study examines how state-level public investments in programming for children and parents' reports of their children's kindergarten readiness.